Romanticism and/or/contra Biedermeier? - Dalibor Tureček (Slovenska Literatura, 2005)
The term Romanticism presents a traditional way of inner structuring and explanation of the history of Czech literature of the 19th century, but this term has been used differently in particular literary historical concepts. The pluralistic concept of Romanticism has not had a firm position in the Czech literary historical context, which is contrarily to the Slovak concept represented by O. Čepan and P. Káša. In the Czech concept Vodička’s model is used, designating the works of Jungmann’s generation as Pre-Romanticism and limiting Romanticism as its subjective, Mácha’s variant. The character of the true Romantic texts does not prove this limited conception. These texts were written in the second period of the national revival but some Romantic features also appeared in the works with syncretistic character, connecting for example Romanticism and Classicism. Biedermeier was understood by the Czech literary historians in the latest years as a negating “contrafacturae” of Romanticism and was used as a synonym for a part of work of the 30s called in the Vodička’s concept “convergion of literature and life”. The translation of German sentimental tragedies of the 20s and the 30s of the 19th century has shown that axiological horizon, basic groups of motives and also typical poetics of Biedermeier have been well known in the Czech environment since the 20s. There were elements of subjective Romanticism co-existing here. Since the 19th century the mutual proportion between the Romanticism and Biedermeier has changed in the Czech culture from a complementary belonging to polemic contradiction. In a modern concept of Czech literature it would be useful to accept the thesis of P. Zajac about pulsating, synoptic character of literary processes as well as to use and in maximal possible measure to extend a subject field of validity of Čepan’s concept of Romanticism as an innerly pluralistic, open structures with wide transitionary zones and possibilities of convergence and meeting with phenomena of different nature.